THE EFFECT OF RUNNING DICTATION MODEL ON STUDENTS’ WRITING ADVERTISEMENT TEXT ABILITY (A Study at the Tenth Grade Students of SMA Negeri 5 Padangsidimpuan) - Sri Ramayani (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The objective of this research is to know whether there is a significant effect of running dictation model on students’ writing advertisement text ability at the tenth grade students of SMA Negeri 5 Padangsidimpuan. This research uses experimental method with pre-experimental research design; one group pre-test post-test design. The population is all of the tenth grade students which consist of 248 students. Technique sampling that used in this research is systematic simple sampling and the number of the sample consists of 30 students. In collecting the data, the writer uses observation sheet to get the data of the application of running dictation model and test to get the data of the students’ writing advertisement text ability. The writer uses statistic process in analyzing by using t test formula. Based on the data that has been analyzed, the result of data analyzing showed that t count is higher than t table (t count 13.2 > t table 2.04). So, the hypothesis is accepted. It means that there is a significant effect of running dictation model on students’ writing advertisement text ability at the tenth grade students of SMA Negeri 5 Padangsidimpuan. Keywords: running dictation model, writing advertisement text ability. Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah ada sebuah pengaruh yang signifikan dari model running dictation terhadap kemampuan siswa dalam menulis teks iklan di kelas sepuluh SMA Negeri 5 Padangsidimpuan. Penelitian ini menggunakan metode eksperimental dengan rancangan penelitian pre-experimental; one group pre-test post-test design. Populasi penelitian terdiri dari 248 siswa kelas sepuluh. Teknik penarikan sampel yang digunakan dalam penelitian ini adalah penarikan sampel sistematis sederhana dan jumlah sample terdiri dari 30 siswa. Dalam pengumpulan data, peneliti menggunakan lembar observasi untuk menjaring data dari pengaplikasian model running dictation dan tes untuk menjaring data mengenai kemampuan siswa dalam menulis teks iklan. Peneliti menggunakan proses statistik dalam analisis data, yaitu rumus tes t. Berdasarkan data yang telah di analisis, hasil anaisis data menunjukkan bahwa t hitung lebih besar daripada t tabel (t hitung 13.2 > t tabel 2.04). Jadi, hipotesis diterima. Hal ini berarti ada sebuah pengaruh yang signifikan dari model running dictation terhadap kemampuan siswa dalam menulis teks iklan di kelas sepuluh SMA Negeri 5 Padangsidimpuan. Kata kunci: model running dictation, kemampuan menulis teks iklan